Electrifying roller for electrophotographic apparatus
By using the elastic body layer of a specific rubber composition in the electronic photographic equipment, the problem of rising resistance and ionic conductors seepage is solved, and the image quality is improved and the durability of the equipment is enhanced.
Patent Information
- Application Number
- CN202380045946.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-05-10
- Publication Date
- 2025-01-21
AI Technical Summary
In the charged rollers of the electrophotography device, continuous application of electrical load will lead to a rise in resistance and the effusion of the ionic conductive agent, which in turn will cause image defects.
An elastomer layer containing a specific rubber composition is used. The rubber composition is composed of chlorohydrin rubber, nitrile rubber, cross-linking agent, ion conductive agent, piperidinyl oxy radical compound, phenolic antioxidant, and salt of cyclic amidine compound. It is composed of a thiophthalimide compound and the coordination and cross-linking of these components to suppress excessive polarization of the ion conductive agent.
Effectively suppress the rising resistance when the resistance and durability and the exudation of ionic conductors, improve the quality of the image and extend the service life of the charged roller.
Smart Images

Figure CN119343637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a charging roller for an electrophotographic device which is suitable for use in an electrophotographic device such as a copying machine, a printer, a facsimile machine, etc. which adopts an electrophotographic method. Background Art
[0002] The charging roller of an electrophotographic device may require an ion conductive mechanism for the sake of electrical uniformity, etc. For example, Patent Document 1 discloses that an ion conductive agent is blended in the base layer of the charging roller.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-132020 Summary of the invention
[0006] Problems to be solved by the invention
[0007] If an electrical load based on energization is continuously applied to the charging roller, the resistance of the charging roller increases, and there is a risk of image defects due to a decrease in charging capacity. This is because if an electrical load is applied to the charging roller, the ion conductive agent in the base rubber of the charging roller is polarized, and the polarization of the ion conductive agent is too fast, so that the polarized anions and cations are excessively biased toward the + electrode side and the - electrode side, respectively, and the ion conductive agent becomes less in the center of the base rubber, forming a high resistance part. If the amount of the ion conductive agent is excessively increased for the purpose of suppressing excessive polarization in the base rubber, there is a risk of causing the ion conductive agent to seep out and cause image defects.
[0008] An object of the present invention is to provide a charging roller for an electrophotographic device that can suppress an increase in resistance during power-on durability and the leakage of an ion conductive agent.
[0009] Means used to solve problems
[0010] The charging roller for an electrophotographic device according to the present invention comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, wherein the elastic layer is a crosslinked body containing the rubber composition described below (a) to (e).
[0011] (a) one or more selected from epichlorohydrin rubber and nitrile rubber
[0012] (b) Cross-linking agent
[0013] (c) Ionic Conductive Agent
[0014] (d) one or more selected from piperidinyloxy free radical compounds and phenolic antioxidants
[0015] (e) one or more selected from the group consisting of salts of cyclic amidine compounds and thiophthalimide compounds
[0016] The (e) is preferably a naphthoate of a cyclic amidine compound. The (e) is preferably N-cyclohexylthiophthalimide. The (c) is preferably an ammonium, phosphonium or imidazolium ion conductor. The (c) is preferably an ion conductor containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom or a perchlorate anion. The rubber composition preferably further contains a specific surface area of 40 m 2 / g and above and 300m 2 / g or less carbon black.
[0017] (1) The charging roller for an electrophotographic device according to the present invention comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, wherein the elastic layer is a crosslinked body containing the rubber composition described below (a) to (e).
[0018] (a) one or more selected from epichlorohydrin rubber and nitrile rubber
[0019] (b) Cross-linking agent
[0020] (c) Ionic Conductive Agent
[0021] (d) one or more selected from piperidinyloxy free radical compounds and phenolic antioxidants
[0022] (e) one or more selected from the group consisting of salts of cyclic amidine compounds and thiophthalimide compounds
[0023] (2) In the above (1), the (e) is preferably a naphthoate salt of a cyclic amidine compound.
[0024] (3) In the above (1), the (e) is preferably N-cyclohexylthiophthalimide.
[0025] (4) In any one of the above (1) to (3), the (c) is preferably an ammonium-based, phosphonium-based or imidazolium-based ion conductive agent.
[0026] (5) In any one of the above (1) to (4), the above (c) is preferably an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
[0027] (6) In any one of the above (1) to (5), the rubber composition preferably further contains a rubber having a specific surface area of 40 m 2 / g and above and 300m 2 / g or less carbon black.
[0028] Effects of the Invention
[0029] According to the charging roller for electronic photographic equipment involved in the present invention, it has a shaft and an elastic layer formed on the outer peripheral surface of the shaft, and the elastic layer is a cross-linked body containing the rubber composition (a) to (e) above, so it can suppress the increase in resistance during power-on durability and the leakage of ion conductive agent.
[0030] When the (e) is a naphthoate of a cyclic amidine compound, the effect of suppressing the increase in resistance during the electrical durability test is particularly excellent.
[0031] In addition, when the above-mentioned (e) is N-cyclohexylthiophthalimide, the effect of suppressing the increase in resistance during the electrical durability test is particularly excellent.
[0032] Moreover, when the (c) is an ammonium, phosphonium or imidazolium ion conductor, the polar group of the rubber component of (a) is easy to coordinate with the cation of the ion conductor, and it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability test, so the effect of suppressing the increase in resistance during the electrical durability test is particularly excellent. In addition, the salt of the cyclic amidine compound and the thiophthalimide compound of (e) are easy to coordinate with the cation of the ion conductor, and it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability test, so the effect of suppressing the increase in resistance during the electrical durability test is particularly excellent. In addition, it is easy to form a low resistance.
[0033] Moreover, the ionic conductive agent comprising the sulfonate anion with fluorine atom or the bis(sulfonyl)imide anion with fluorine atom contains a large amount of fluorine groups in the structure, so the alkalinity of the anion itself is small, and a relatively weak ionic bond is formed with the cation. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber of (a), and are easy to form low resistance. In addition, these anions are all hydrophobic, and hygroscopicity is also low even in a high humidity environment. Therefore, the effect of suppressing the change of resistance caused by environmental changes is excellent. Moreover, the ionic conductive agent comprising the perchlorate anion is easy to form low resistance.
[0034] Furthermore, the rubber composition further comprises a 2 / g and above and 300m 2 When the carbon black content is less than 30%, the effect of suppressing the leakage of the ion conductive agent is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its AA line cross-sectional view. DETAILED DESCRIPTION
[0036] The charging roller for an electrophotographic apparatus (hereinafter, sometimes simply referred to as a charging roller) according to the present invention will be described in detail. Figure 1 (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its AA line cross-sectional view.
[0037] The charged roller 10 includes a shaft 12, an elastomer layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastomer layer 14. The elastomer layer 14 is a layer (base layer) that becomes the base of the charged roller 10. The surface layer 16 is a layer that appears on the surface of the charged roller 10. In addition, in the charged roller of the present invention, it is also possible to have a structure without a surface layer. That is, the charged roller may also be a charged roller that includes a shaft 12 and an elastomer layer 14 formed on the outer peripheral surface of the shaft 12 and does not have a surface layer 16 on the outer peripheral surface of the elastomer layer 14.
[0038] The shaft body 12 is not particularly limited as long as it has conductivity. Specifically, examples thereof include a core rod made of a solid body or a hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, a primer, or the like may be applied to the surface of the shaft body 12 as required. In other words, the elastomer layer 14 may also be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, the primer, or the like may also be made conductive as required.
[0039] The elastic layer 14 is composed of a crosslinked body containing the rubber composition described below (a) to (e).
[0040] (a) one or more selected from epichlorohydrin rubber and nitrile rubber
[0041] (b) Cross-linking agent
[0042] (c) Ionic Conductive Agent
[0043] (d) one or more selected from piperidinyloxy free radical compounds and phenolic antioxidants
[0044] (e) one or more selected from the group consisting of salts of cyclic amidine compounds and thiophthalimide compounds
[0045] Examples of epichlorohydrin rubber include homopolymers of epichlorohydrin (CO), epichlorohydrin-ethylene oxide copolymers (ECO), epichlorohydrin-allyl glycidyl ether copolymers (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymers (GECO). Among them, ECO and GECO containing ethylene oxide as a copolymer component are more preferred in terms of easy acquisition of low-resistance bodies compared to epichlorohydrin rubbers that do not contain ethylene oxide as a copolymer component. In addition, GCO and GECO containing allyl glycidyl ether as a copolymer component have double bonds, and therefore are more preferred in terms of being less prone to aging than epichlorohydrin rubbers that do not contain allyl glycidyl ether as a copolymer component.
[0046] Nitrile rubber is acrylonitrile-butadiene rubber (NBR). Nitrile rubber is softer than epichlorohydrin rubber, so there is a surface in the rubber where the ion conductive agent is more easily moved. In this case, the resistance rise during the power-on durability and the seepage of the ion conductive agent can also be suppressed by the structure of the present invention. In addition, in the case of containing nitrile rubber as (a), it is easy to adjust the hardness of the elastomer layer 14.
[0047] The crosslinking agent is not particularly limited. Examples of the crosslinking agent include sulfur crosslinking agents, peroxide crosslinking agents, and dechlorination crosslinking agents. These crosslinking agents may be used alone or in combination of two or more.
[0048] Examples of the sulfur crosslinking agent include sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and high-molecular polysulfide.
[0049] Examples of the peroxide crosslinking agent include peroxyketals, dialkyl peroxides, peroxyesters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.
[0050] As a peroxide crosslinking agent, from the viewpoint of relatively high decomposition temperature and easy molding at higher temperature, it is preferred that the decomposition temperature in the thermal storage test (BAM formula: SADT) is 60°C or higher and the 1-minute half-life temperature is 150°C or higher. More preferably, the 1-minute half-life temperature is 160°C or higher, and further preferably, the 1-minute half-life temperature is 170°C or higher. On the other hand, from the viewpoint of excellent crosslinking speed, the 1-minute half-life temperature is preferably 200°C or lower. More preferably, the 1-minute half-life temperature is 190°C or lower, and further preferably, the 1-minute half-life temperature is 180°C or lower.
[0051] Preferred peroxide crosslinking agents include peroxyketals, dialkyl peroxides, and peroxyesters. Examples of peroxyketals include 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, and n-butyl 4,4-di(tert-butylperoxy)valerate. Examples of dialkyl peroxides include di(2-tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne. Examples of the peroxyester include tert-butyl peroxybenzoate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxylaurate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-hexyl peroxyisopropyl monocarbonate, etc. Among them, di(2-tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, etc. are preferred from the viewpoints that unreacted components are less likely to remain and the boiling point of the decomposition product is relatively low, making it easy to remove the decomposition product.
[0052] Examples of the dechlorination crosslinking agent include dithiocarbonate compounds, and more specifically, include quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, and 5,8-dimethylquinoxaline-2,3-dithiocarbonate.
[0053] The amount of the crosslinking agent is preferably within a range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, relative to 100 parts by mass of the (a) specific polar rubber, from the viewpoint of preventing bleeding.
[0054] From the viewpoint of making it easy to form the elastomer layer 14 with low hardness, the content of the peroxide crosslinking agent is preferably 6 parts by mass or less relative to 100 parts by mass of the component (a) in terms of the amount of the peroxide precursor. It is more preferably 5 parts by mass or less, and further preferably 4 parts by mass or less. In addition, from the viewpoint of excellent crosslinking degree of the rubber and not easy to age, it is preferably 0.2 parts by mass or more relative to 100 parts by mass of the component (a) in terms of the amount of the peroxide precursor. It is more preferably 0.4 parts by mass or more, and further preferably 0.6 parts by mass or more.
[0055] The ion conductive agent is not particularly limited. It can be any ion conductive agent used in the field of electronic photographic equipment. Examples of the ion conductive agent include quaternary ammonium salts, quaternary phosphonium salts, imidazolium salts, borates, surfactants, etc. Among them, quaternary ammonium salts, quaternary phosphonium salts, and imidazolium salts are particularly preferred.
[0056] Examples of cations of quaternary ammonium salts include cations having one or more alkyl or aryl groups having carbon atoms of about 1 to 18 (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.). The alkyl or aryl group of the cation of the quaternary ammonium salt preferably has carbon atoms of 1 to 10. Examples of anions of the quaternary ammonium salts include F - , Cl - Br - ,I - Halogen ions, ClO 4- , BF 4- PF 6- 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 - 、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the quaternary ammonium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0057] Examples of quaternary phosphonium salt cations include cations having one or more alkyl or aryl groups (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.) with carbon atoms of 1 to 18. The alkyl or aryl group of the quaternary phosphonium salt cation preferably has carbon atoms of 1 to 10. Examples of quaternary phosphonium salt anions include F - , Cl - Br - 、I- and other halogen ions、ClO 4- , BF 4- PF 6- 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 -、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 - 、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the quaternary phosphonium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0058] Examples of the imidazolium salt include unsubstituted imidazolium salts, 1-alkylimidazolium salts, 3-alkylimidazolium salts, 1,3-dialkylimidazolium salts, and 1,2,3-trialkylimidazolium salts. More specifically, for example, 1-methylimidazolium salt, 1,3-dimethylimidazolium salt, 1,3-diethylimidazolium salt, 1,3-dipropylimidazolium salt, 1,3-dibutylimidazolium salt, 1,3-dicyclohexylimidazolium salt, 1-ethyl-3-methylimidazolium salt, 1-propyl-3-methylimidazolium salt, 1-butyl-3-methylimidazolium salt, 1-hexyl-3-methylimidazolium salt, 1-ethyl-2,3-dimethylimidazolium salt, 1-propyl-2,3-dimethylimidazolium salt, 1-butyl-2,3-dimethylimidazolium salt, etc. can be mentioned. Examples of the anion of the imidazolium salt include F - , Cl - Br - ,I - Halogen ions, ClO4 - 、BF4 - PF6 - 、SO4 2- 、HSO4 - 、C2H5SO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - CF3(CF2)3SO3 - 、(CF3SO2)3C - CF3(CF2)2COO - As the anion of the imidazolium salt, ClO4 is more preferred - 、(CF3SO2)2N - CF3SO3 - wait.
[0059] As borates, for example, borates having one or more alkyl or aryl groups having a carbon number of about 1 to 18 (methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.) and containing alkali metal ions or alkaline earth metal ions such as lithium ions, sodium ions, potassium ions, and calcium ions can be shown.
[0060] From the viewpoint of low resistance, the content of the ion conductive agent is preferably 0.1 parts by mass or more relative to 100 parts by mass of component (a). More preferably, it is 0.3 parts by mass or more, and further preferably, it is 0.5 parts by mass or more. In addition, from the viewpoint of easily suppressing the seepage of the ion conductive agent, it is preferably 5.0 parts by mass or less relative to 100 parts by mass of component (a). More preferably, it is 3.0 parts by mass or less, and further preferably, it is 2.0 parts by mass or less.
[0061] The piperidinyloxy radical compound functions as a delay agent in cross-linking. The piperidinyloxy radical compound maintains a state of equilibrium with the free radicals generated by the thermal decomposition of the cross-linking agent. In the initial stage of cross-linking when the amount of free radicals generated is relatively small, the piperidinyloxy radical compound maintains a state of equilibrium with the free radicals generated, inhibiting the cross-linking reaction (delaying the start time (T10) of cross-linking). On the other hand, by increasing the cross-linking temperature, the cross-linking speed can be accelerated. Thus, only the start time (T10) of cross-linking is delayed, without delaying the speed (T90) of the entire cross-linking. By adjusting the cross-linking speed in this way, the molecular arrangement of the polymer is controlled. Since gaps for the ions of the ion conductor to enter are appropriately generated in the polymer, the polar groups of the polymer can coordinate appropriately with the ions of the ion conductor. Thus, even if an electrical load caused by energization is applied, the excessive polarization of the ion conductor can be suppressed. In addition, by delaying T10, before the curing of the rubber is carried out, the salt of the cyclic amidine compound can be uniformly diffused into the rubber by thermal diffusion. As a result, the ion conductive agent is uniformly dispersed in the rubber, so even if an electrical load caused by energization is applied, the excessive polarization of the ion conductive agent can be suppressed. In addition, T10 is the time (s) to reach 10% of the maximum torque at the molding temperature (crosslinking temperature), and T90 is the time (s) to reach 90% of the maximum torque at the molding temperature (crosslinking temperature).
[0062] The piperidinyloxy radical compound is a compound represented by the following general formula (1).
[0063] [Chemistry 1]
[0064]
[0065] Examples of R1 to R4 include hydrogen and alkyl groups having 1 to 4 carbon atoms. Examples of R5 include hydrogen, alkyl groups having 1 to 4 carbon atoms, aryl groups, aryl groups, acetoxy groups, benzyloxy groups, carboxylic acid groups, acetamide groups, and aldehyde groups.
[0066] Preferred piperidinyloxy radical compounds include 2,2,6,6-tetramethylpiperidinyloxy radical, 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-benzoyloxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-acetamide-2,2,6,6-tetramethylpiperidinyloxy radical, etc. Among them, 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-benzoyloxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-acetamide-2,2,6,6-tetramethylpiperidinyloxy radical, etc. are more preferred from the viewpoints of the melting point being within the optimal range with respect to the molding temperature of the rubber, the radical scavenging ability, the storage stability, the price, etc.
[0067] The phenolic antioxidants exert the same effects as the piperidinyloxy free radical compounds in the reaction system of the present invention. That is, only the crosslinking start time (T10) is delayed, without delaying the overall crosslinking speed (T90). As the phenolic antioxidants, hindered phenolic antioxidants can be used. In addition, monophenolic, diphenolic, triphenolic and polyphenolic antioxidants can be used.
[0068] Examples of hindered phenol antioxidants include 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine. -2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4',4"-[(2,4,6-tri)methylbenzene-1,3,5-triyl]tri(methylene)tris(2,6-di-tert-butylphenol), etc.
[0069] The content of (d) is preferably 0.05 parts by mass or more relative to 100 parts by mass of the component (a), from the viewpoint of being suitable for adjusting the crosslinking speed, etc. More preferably, it is 0.1 parts by mass or more, and even more preferably, it is 0.2 parts by mass or more. In addition, it is preferably 3.0 parts by mass or less relative to 100 parts by mass of the component (a), more preferably, it is 2.0 parts by mass or less, and even more preferably, it is 1.0 parts by mass or less.
[0070] The cyclic amidine compound is a cyclic compound containing an amidine structure in its structure. The salt of the cyclic amidine compound has a moderate polarity capable of coordinating with the ions (cations) of the ion conductive agent. By coordinating the salt of the cyclic amidine compound with the ions of the ion conductive agent, even if an electric load caused by energization is applied, the excessive polarization of the ion conductive agent can be suppressed. The cyclic amidine compound effectively exerts the above-mentioned effect in the state of the salt.
[0071] As the cyclic amidine compound, from the viewpoint of availability, a bicyclic amidine compound is preferred. Examples of the cyclic amidine compound include diazabicycloundecene (1,8-diazabicyclo (5.4.0) undec-7-ene), diazabicyclononene (1,5-diazabicyclo (4.3.0)-5-nonene), etc. As the cyclic amidine compound, from the viewpoint of cation coordination ability, storage stability, etc., diazabicycloundecene is more preferred.
[0072] Examples of the salt of the cyclic amidine compound include naphthoic acid salts of the cyclic amidine compound, phenolic resin salts of the cyclic amidine compound, aliphatic carboxylates, phenolates, borates, etc. As the salt of the cyclic amidine compound, naphthoic acid salts of the cyclic amidine compound are more preferred from the viewpoint of small resistance increase caused by polarization of the ion conductive agent during electrical durability.
[0073] The thiophthalimide compound is a compound containing a thiophthalimide structure in its structure. In the reaction system of the present invention, the thiophthalimide compound exerts the same effect as the salt of the cyclic amidine compound. That is, the thiophthalimide compound has a moderate polarity that can coordinate with the ions of the ion conductor, and by coordinating with the ions of the ion conductor, even if an electric load caused by energization is applied, the excessive polarization of the ion conductor can be suppressed. As the thiophthalimide compound, N-cyclohexylthiophthalimide, N-trifluoromethylthiophthalimide, N-phenylthiophthalimide, N, N'-thiodiphthalimide, etc. can be cited.
[0074] The content of (e) is preferably 0.1 parts by mass or more relative to 100 parts by mass of component (a) from the viewpoint of excellent effect of suppressing excessive polarization of the ion conductive agent even if an electric load caused by energization is applied. More preferably, it is 0.5 parts by mass or more, and further preferably, it is 1.0 parts by mass or more. In addition, from the viewpoint of suppressing the seepage of (e), it is preferably 5.0 parts by mass or less relative to 100 parts by mass of component (a). More preferably, it is 4.0 parts by mass or less, and further preferably, it is 3.0 parts by mass or less.
[0075] The rubber composition may contain other additives as required. Examples of other additives include electronic conductive agents, lubricants, antioxidants, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, fillers, dispersants, pigments, and mold release agents.
[0076] Examples of the electron conductive agent include carbon black, graphite, conductive titanium oxide, conductive zinc oxide, and conductive tin oxide.
[0077] The rubber composition preferably also contains carbon black. Carbon black can suppress the leakage of the ion conductive agent by adsorbing the cations of the ion conductive agent. Carbon black having a specific surface area within a specific range can preferably be used. The larger the specific surface area of the carbon black, the easier it is to adsorb the cations of the ion conductive agent. On the other hand, the larger the specific surface area, the easier it is to cause the carbon black to aggregate, and the easier it is for the conductivity to decrease. Therefore, from the balance between the effect of suppressing the leakage of the ion conductive agent and the effect of suppressing the decrease in conductivity, the specific surface area of the carbon black is preferably 40m 2 / g and above and 300m 2 / g or less. More preferably 42m 2 / g and above and 240m 2 The specific surface area of carbon black can be measured by a nitrogen adsorption method.
[0078] Considering the hardness and conductivity of the elastic layer 14, the content of carbon black is preferably 5 parts by mass or more and 40 parts by mass or less, and more preferably 10 parts by mass or more and 30 parts by mass or less, based on 100 parts by mass of the component (a).
[0079] The thickness of the elastic layer 14 is not particularly limited, but is preferably within a range of 0.1 to 10 mm, more preferably within a range of 0.5 to 5 mm, and even more preferably within a range of 1 to 3 mm.
[0080] The volume resistivity of the elastic layer 14 is not particularly limited, but is preferably 10 2 ~10 10 Ω·cm, more preferably 10 3 ~10 9 Ω·cm, more preferably 10 4 ~10 8 In the range of Ω·cm.
[0081] The surface layer 16 can function as a protective layer of the roller surface. The surface layer 16 preferably contains a polymer component such as polyamide, polyurethane, acrylic resin, alkyd resin, phenolic resin, fluororesin, silicone resin, or a modified product thereof as a main material. Examples of the modified group in the modified product include N-methoxymethyl, silicone group, fluoro group, etc. These polymer components can be included as the surface layer material alone or in combination of two or more. The polymer component of the surface layer 16 can be cross-linked.
[0082] In order to impart conductivity, conductive agents such as carbon black, graphite, conductive titanium oxide, conductive zinc oxide, conductive tin oxide, ion conductive agents (quaternary ammonium salts, borates, surfactants, etc.) may be appropriately added to the surface layer 16. In addition, various additives may be appropriately added as needed. In addition, in order to ensure surface roughness, roughness forming particles may also be added.
[0083] The roughness forming particles form surface irregularities in the surface layer 16. Examples of the roughness forming particles include resin particles, silica particles, and the like. Examples of the resin particles include urethane particles, silicone particles, acrylic particles, and the like. The average particle size of the roughness forming particles is preferably in the range of 3 to 50 μm. The average particle size of the roughness forming particles can be calculated by the median particle size using a laser diffraction particle size distribution measuring device.
[0084] The thickness of the surface layer 16 is not particularly limited, but is preferably in the range of 0.01 to 100 μm, more preferably in the range of 0.1 to 20 μm, and even more preferably in the range of 0.3 to 10 μm. 7 ~10 12 Ω·cm, more preferably 10 8 ~10 11 Ω·cm, more preferably 10 9 ~10 10 In the range of Ω·cm.
[0085] The charging roller 10 can be manufactured, for example, as follows. First, the shaft 12 is coaxially disposed in the hollow portion of a roller forming mold, a rubber composition is injected, and the rubber composition is heated, cured, and then demolded, or the rubber composition is extruded on the surface of the shaft 12, thereby forming an elastic body layer 14 on the periphery of the shaft 12. Next, a surface layer forming composition is applied to the periphery of the formed elastic body layer 14, and ultraviolet irradiation and heat treatment are performed as needed to form a surface layer 16. In this way, the charging roller 10 can be manufactured.
[0086] The surface layer forming composition contains the above-mentioned main material, conductive agent, and other additives contained as needed. As other additives, crosslinking agents, leveling agents, surface modifiers, etc. of polymer components can be listed. From the viewpoint of adjusting viscosity, the surface layer forming composition can appropriately include organic solvents such as methyl ethyl ketone, toluene, acetone, ethyl acetate, butyl acetate, methyl isobutyl ketone (MIBK), THF, DMF, methanol, ethanol, etc. Water-soluble solvents and other solvents. As a coating method, various coating methods such as roller coating, dipping, and spraying can be applied.
[0087] According to the charged roller 10 constructed as above, the elastomer layer 14 is composed of a crosslinked body of the rubber composition containing the above (a) to (e), so that the resistance rise during the power-on durability and the seepage of the ion conductor can be suppressed. It is speculated that this is due to the following mechanism. That is, by the ion coordination of the salt of the cyclic amidine compound, the thiophthalimide compound and the ion conductor, even if the electric load caused by power-on is applied, the excessive polarization of the ion conductor can be suppressed. In addition, the piperidinyloxy radical compound and the phenolic antioxidant only delay the crosslinking start time (T10) when crosslinking chlorohydrin rubber and nitrile rubber, butadiene acrylonitrile rubber, without delaying the overall crosslinking speed (T90). By adjusting the crosslinking speed in this way, the molecular arrangement of the polymer is controlled. Since the gaps for the ions of the ion conductor to enter are appropriately generated in the polymer, the polar groups of the polymer can be appropriately coordinated with the ions of the ion conductor. Thus, even if the electric load caused by power-on is applied, the excessive polarization of the ion conductor can be suppressed. In addition, by delaying T10, before the curing of the rubber is carried out, the salt of the cyclic amidine compound can be uniformly diffused into the rubber by thermal diffusion. As a result, the ion conductor is uniformly dispersed in the rubber, so even if the electric load caused by the energization is applied, the excessive polarization of the ion conductor can be suppressed. According to the above, the resistance rise during the energization durability can be suppressed. In addition, the excessive polarization of the ion conductor is not suppressed by the increment of the ion conductor, so the seepage of the ion conductor can also be suppressed. In addition, by making the salt of the cyclic amidine compound, the thiophthalimide compound and the ion coordination of the ion conductor, only delaying the crosslinking start time (T10) without delaying the speed of the whole crosslinking (T90), the gap for the ions of the ion conductor to enter is appropriately generated in the polymer, and the polar group of the polymer is appropriately coordinated with the ions of the ion conductor, so that the ion conductor is less likely to seep out, so even if the amount of the ion conductor is increased, the seepage of the ion conductor can be suppressed.
[0088] Moreover, if the ion conductor is an ammonium, phosphonium or imidazolium series, the polar group of the rubber component (a) is easy to coordinate with the cation of the ion conductor, and it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, the salt of the cyclic amidine compound and the thiophthalimide compound (e) are easy to coordinate with the cation of the ion conductor, and it is also easy to suppress the excessive polarization of the ion conductor during the electrical durability, so the effect of suppressing the resistance increase during the electrical durability is particularly excellent. In addition, it is easy to form a low resistance.
[0089] Moreover, if the ionic conductive agent is an ionic conductive agent comprising a sulfonate anion with a fluorine atom or a bis(sulfonyl)imide anion with a fluorine atom, a large amount of fluorine groups are contained in the structure, so the alkalinity of the anion itself is small, and a relatively weak ionic bond is formed with the cation. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber of (a), and are easy to form low resistance. In addition, these anions are all hydrophobic, and their hygroscopicity is also low even in a high humidity environment. Therefore, the effect of suppressing the change of resistance caused by environmental changes is excellent. Moreover, the ionic conductive agent comprising a perchlorate anion is easy to form a low resistance.
[0090] Example
[0091] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples.
[0092] (Experimental Example 1)
[0093] <Preparation of Rubber Composition>
[0094] 100 parts by mass of epichlorohydrin rubber (ECO), 3 parts by mass of a peroxide crosslinking agent (PEROXYMON F40) (1.2 parts by mass in terms of original mass), 0.2 parts by mass of a piperidinyloxy radical compound (4-hydroxyTEMPO radical), 5 parts by mass of an acid scavenger, 1 part by mass of an ion conductive agent, and 0.1 parts by mass of a salt of a cyclic amidine compound (naphthoate of diazabicycloundecene) were stirred and mixed using a stirrer to prepare a rubber composition.
[0095] <Formation of Elastomer Layer>
[0096] A mandrel (6 mm in diameter) was placed in the mold, the rubber composition was injected at 120°C, and heated at 175°C for 30 minutes to crosslink the rubber composition. After that, the rubber composition was cooled and demolded to form an elastic layer with a thickness of 2 mm on the outer periphery of the mandrel.
[0097] <Formation of the Surface Layer>
[0098] 100 parts by mass of N-methoxymethylated nylon ("EF30T" manufactured by Nagase Fine Chemicals), 60 parts by mass of conductive tin oxide ("S-2000" manufactured by Mitsubishi Materials), 1 part by mass of citric acid, and 300 parts by mass of methanol were mixed to prepare a surface layer forming composition. Next, the surface layer forming composition was roll-coated on the surface of the elastomer layer and heated at 120°C for 50 minutes to form a surface layer with a thickness of 10 μm on the periphery of the elastomer layer. Thus, the charging roller involved in Example 1 was produced.
[0099] (Experimental Example 2)
[0100] A charging roller was produced in the same manner as in Experimental Example 1 except that the blending amount of the salt of the cyclic amidine compound was changed in the preparation of the rubber composition.
[0101] (Experimental Examples 3-4)
[0102] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 1 except that the blending amounts of the salt of the cyclic amidine compound and the piperidinyloxy radical compound were changed.
[0103] (Experimental Examples 5-6)
[0104] A charging roller was produced in the same manner as in Experimental Example 1 except that the type and amount of the salt of the cyclic amidine compound were changed in the preparation of the rubber composition.
[0105] (Experimental Example 7)
[0106] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 1 except that a thiophthalimide compound was used instead of the salt of the cyclic amidine compound and the blending amount thereof was changed.
[0107] (Experimental Example 8)
[0108] A charging roller was produced in the same manner as in Experimental Example 1 except that nitrile rubber (NBR) was used in place of epichlorohydrin rubber (ECO) in the preparation of the rubber composition and the blending amount of the cyclic amidine compound was changed.
[0109] (Experimental Example 9)
[0110] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 1 except that a phenolic antioxidant was used instead of the piperidinyloxy radical compound and the blending amount thereof was changed, and further, the blending amount of the cyclic amidine compound was changed.
[0111] (Experimental Example 10)
[0112] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 1 except that the blending amount of the salt of the cyclic amidine compound and the blending amount of the ion conductive agent were changed.
[0113] (Experimental Examples 11-12)
[0114] A charging roller was produced in the same manner as in Experimental Example 10 except that the type of the ion conductive agent was changed in the preparation of the rubber composition.
[0115] (Experimental Example 13)
[0116] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 1 except that the blending amount of the salt of the cyclic amidine compound was changed and carbon black was further blended.
[0117] (Experimental Example 21)
[0118] A charging roller was produced in the same manner as in Experimental Example 1, except that the salt of the cyclic amidine compound and the piperidinyloxy radical compound were not added in the preparation of the rubber composition.
[0119] (Experimental Example 22)
[0120] A charging roller was produced in the same manner as in Experimental Example 21 except that the amount of the ion conductive agent was increased in the preparation of the rubber composition.
[0121] (Experimental Examples 23 to 26)
[0122] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Examples 4 to 7, except that the piperidinyloxy radical compound was not blended.
[0123] (Experimental Example 27)
[0124] A charging roller was produced in the same manner as in Experimental Example 4, except that the salt of the cyclic amidine compound was not blended in the preparation of the rubber composition.
[0125] (Experimental Example 28)
[0126] In the preparation of the rubber composition, a charging roller was produced in the same manner as in Experimental Example 9 except that the salt of the cyclic amidine compound was not blended and the blending amount of the phenolic antioxidant was changed.
[0127] As materials for the elastic layer-forming composition, the following materials were prepared.
[0128] ・Epichlorohydrin rubber (ECO): Epichlomer CG102 manufactured by Osaka Soda
[0129] Nitrile rubber (NBR): "Nipol DN3335" manufactured by Japan Zeon
[0130] · Cross-linking agent: NOF Corporation's "PEROXYMON F40"
[0131] ·Diazabicycloundecene salt <1> :1,8-diazabicyclo(5.4.0)undec-7-ene, 3-hydroxy-2-naphthoate
[0132] ·Diazabicycloundecene salt <2> :1,8-diazabicyclo(5.4.0)undec-7-ene phenolic resin salt
[0133] ·Diazabicyclononene salt: 1,5-diazabicyclo(4.3.0)-5-nonene phenolic resin salt
[0134] ·Thiophthalimide compounds: N-cyclohexylthiophthalimide
[0135] Piperidinyloxy free radical compounds: 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy free radical
[0136] Phenolic antioxidant: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate
[0137] Acid absorbent: "DHT-4A" manufactured by Kyowa Chemical Industry
[0138] Ionic conductive agent <1> :Tetrabutylammonium trifluoromethanesulfonate manufactured by Tokyo Chemical Industry
[0139] Ionic conductive agent <2> :The following phosphonium salts (synthetic products)
[0140] Ionic conductive agent <3> :1-Ethyl-3-methylimidazolium bromide manufactured by Shikoku Chemical Industry Co., Ltd.
[0141] Carbon black: SEAST9 manufactured by Tokai Carbon (specific surface area 142 m 2 / g)
[0142] <Synthesis of Phosphonium Salt>
[0143] Tri-n-butyldodecylphosphonium bromide and bis(trifluoromethanesulfonyl)imidic acid were added to a mixed solution of dichloromethane:ion exchange water (1:1), and the mixture was stirred at room temperature for 4 hours to obtain tri-n-butyldodecylphosphonium=bis(trifluoromethanesulfonyl)imide from the organic layer.
[0144] The produced charging roller was evaluated for resistance change during power-on durability and bleed-out of the ion conductive agent.
[0145] <Evaluation method for change in on-resistance>
[0146] exist A load of 700 g is applied to each end of the charged roller on a metal drum, and the metal drum is rotated at 90 rpm. The current is applied to the test in a manner that the cumulative current is 20,000 μA h. The resistance value before and after the test is obtained, and the resistance change is calculated in bits. The case where the resistance change is less than 0.7 bits is evaluated as "A", the case where the resistance change is more than 0.7 bits and less than 1.0 bits is evaluated as "B", and the case where the resistance change is more than 1.0 bits is evaluated as "C".
[0147] <Bleeding Evaluation Method>
[0148] After the charging roller was left in a hot and humid environment at 40° C. for 30 days, the presence or absence of oozing out on the surface of the charging roller was observed. The case where no oozing out was observed was evaluated as “A”, and the case where oozing out was observed was evaluated as “B”.
[0149]
[0150] Table 2
[0151]
[0152] In Experimental Examples 1 to 13, in the preparation of the rubber composition, one or more selected from epichlorohydrin rubber and nitrile rubber, a crosslinking agent, an ion conductive agent, one or more selected from piperidinyloxy radical compounds and phenolic antioxidants, and one or more selected from salts of cyclic amidine compounds and thiophthalimide compounds were added, and the resistance increase caused by polarization of the ion conductive agent during the electrical durability test was small. In addition, no oozing of the ion conductive agent was observed.
[0153] In Experimental Example 21, in the preparation of the rubber composition, the salt of the cyclic amidine compound, the thiophthalimide compound, the piperidinyloxy radical compound, and the phenolic antioxidant were not added, and the resistance increase caused by the polarization of the ion conductive agent during the electrical durability test was large. In Experimental Example 22, although the resistance increase during the electrical durability test was suppressed by the increase in the amount of the ion conductive agent, the seepage of the ion conductive agent was observed. In Experimental Examples 23 to 26, in the preparation of the rubber composition, the piperidinyloxy radical compound and the phenolic antioxidant were not added, and the resistance increase caused by the polarization of the ion conductive agent during the electrical durability test was slightly large. In Experimental Examples 27 to 28, in the preparation of the rubber composition, the salt of the cyclic amidine compound and the thiophthalimide compound were not added, and the resistance increase caused by the polarization of the ion conductive agent during the electrical durability test was large.
[0154] As mentioned above, although embodiment and Example of this invention were described, this invention is not limited at all to the said embodiment and Example, Various changes can be made in the range which does not deviate from the summary of this invention.
[0155] Description of Reference Numerals
[0156] 10: Charging roller;
[0157] 12: Axis;
[0158] 14: Elastomer layer;
[0159] 16: Surface.
Claims
1. A charging roller for an electrophotographic device, wherein: The charging roller for an electrophotographic device comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body. The elastic layer is a crosslinked body containing the rubber composition of the following (a) to (e), (a) one or more selected from epichlorohydrin rubber and nitrile rubber, (b) a cross-linking agent, (c) an ion conductive agent, (d) one or more selected from piperidinyloxy free radical compounds and phenolic antioxidants, (e) one or more selected from salts of cyclic amidine compounds and thiophthalimide compounds.
2. The charging roller for an electrophotographic apparatus according to claim 1, wherein The (e) is a naphthoate salt of a cyclic amidine compound.
3. The charging roller for an electrophotographic apparatus according to claim 1, wherein The (e) is N-cyclohexylthiophthalimide.
4. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 3, wherein The (c) is an ammonium-based, phosphonium-based or imidazolium-based ion conductive agent.
5. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 4, wherein The (c) is an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
6. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 5, wherein The rubber composition also contains a specific surface area of 40m 2 / g and above and 300m 2 / g or less carbon black.
Citation Information
Patent Citations
Rubber composition for conductive roller
JP2002132020A